FPGA Module for Fast Waveform Generation and Synchronous Data Acquisition - Eliáš, Josef (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This article deals with system for fast waveform generation and synchronous data acquisition. System is used for evaluation of optical sensors by sweep through narrow band light source. The DAQ system use dual core ARM processor with build in FPGA array. We can achieve direct sharing memory between ARM core and AD/DA periphery through SoC architecture. Then we can optimally distributed core usage between processors and peripherals.
Keywords: waveform; data aquisition; FPGA; SoC; ARM; AXI